Efficacy and Safety of Drug-Eluting Bead Bronchial Arterial Chemoembolization Plus Anlotinib in Patients With Advanced Non-small-Cell Lung Cancer - Liu, Juanfang; Zhang, Wenguang; Ren, Jianzhuang; Li, Zhen; Lu, Huibin; Sun, Zhanguo; Han, Xinwei (Frontiers in Cell and Developmental Biology, 2021)
Aim：To determine the efficacy and safety of the combination therapy of drug-eluting bead bronchial arterial chemoembolization plus anlotinib oral administration in the treatment of non–small-cell lung cancer. Methods: Consecutive data of 51 patients with advanced non–small-cell lung (NSCLC) were retrospectively collected from February 2018 to August 2019. All patients underwent drug-eluting bead bronchial arterial chemoembolization (DEB-BACE) followed by anlotinib treatment. Overall survival (OS) and progression-free survival (PFS) were calculated and analyzed using the Kaplan–Meier method and log-rank test, and factors associated with OS and PFS were assessed by Cox proportional-hazards test. Treatment response at 30 d was assessed by enhanced CT, then objective response rate (ORR) and disease control rate (DCR) were calculated. Treatment related adverse events (TRAEs) were also evaluated. Results: The median overall survival (OS) was 18.4 months (95% CI, 16.6-20.2 months) and progression-free survival (PFS) was 8.4 months (95% CI, 6.2-10.6 months). The objective response rate (ORR) and disease control rate (DCR) for the whole cohort were 21.6% and 100% at 30 d after the first cycle of treatment. Most of the treatment-related adverse reactions were mild and moderate including anorexia, hypertension, fatigue and hand-foot syndrome. Only 8 (15.7%) patients developed to grade 3-4. No deaths or other serious adverse reactions occurred. Both TNM stage and brain metastasis were independent risk factors for OS and PFS. Conclusion: Drug-eluting bead bronchial arterial chemoembolization (DEB-BACE) concomitant with anlotinib has promising efficacy as well as tolerable toxicity in patients with advanced non–small-cell lung cancer.